Digital supply chain: critical factors related to the digital transformation in supply chain - Ribeiro, Marcos Novais (2026)
This study investigates the critical factors that enable and leverage digital transformation in supply chain, addressing two main objectives: identify key factors from literature and investigate their application in a real-world case study. To the first objective, a systematic literature review revealed 24 factors, grouped into seven clusters: organizational strategy, supply chain operations, information technology, people, organizational culture, financial, government policies and sustainability. This clusters were organized into internal and external dimensions within a conceptual framework illustrating their nterdependencies. To accomplish the second objective, a single case study of a multinational company was researched in the active execution phase of digital transformation in supply chain, data collection included semi-structured interviews and company documentation, through a multi approach that involves FCA/CHD (Iramuteq) textual analysis as well qualitative analysis from interviews. 8 critical factors were identified being: supply chain strategy, organizational structure, supply chain integration, I4.0 technologies, data governance, collaboration, financial gains and sustainability that appeared the most prominent and relevance, not only being critical, but driving and influencing the overall digital supply chain transformation, these factors were classified as critical driving factors. While these critical driving factors are essential to drive a digital supply chain transformation, it was also recognized that other factors along of a digital supply chain initiative could emerge as critical factors depending on context and aspects that the company is inserted. Based on these results, this research is proposing a digital supply chain factors assessment framework, that distinguishes critical driving factors and eligible factors towards the digital supply chain implementation journey. Considering the different aspects and context, the purpose of the framework is to assist practitioners or company executives who want to drive or initiate a digital supply chain initiative and evaluate or assess it. The 24 factors in literature have a broad view and in different areas related to supply chain and can provide a concrete view of what must be managed or prioritized toward a digital supply chain program.